Evaluation of prescriptions using WHO indicators in public health care sector of Dhaka, Bangladesh - Abir, Md. Wasiq Dayem Minhazul Kabir (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.